The Impact Of Human Resources Management Strategies On The Strategic Agility: A Field Study In Large And Medium Yemeni Manufacturing Sector - Maged Mohammed Barahma; Mohammad Nashief; Mohammed Ali Al-Awlaqi; Kalsom Ali (Creative Commons Attribution 4.0 International Lic, 2024)
Non-Indexed Publication